Variations in Qira'at Science and Their Implications for the Interpretation of the Al-Qur'an and Islamic Legal Istinbat - Fairuz Amin Fuadi (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the implications of variations in the science of Qira'at for Quranic interpretation and the Istinbat of Islamic law. Qira'at, as a discipline that studies various readings of the Quran, reflects the diversity of Islamic scholarly traditions and demonstrates the complexity of understanding the sacred text. This study employed a qualitative approach using library research methods through a review of classical and contemporary literature, including books on Qira'at, tafsir, and ushul fiqh. Data analysis was conducted using content analysis and descriptive techniques to identify the relationship between differences in readings and changes in meaning that influence the process of interpretation and the determination of Islamic law. The results show that variations in Qira'at are not only related to phonetics but also affect the meaningful structure of verses, which in some cases has implications for different legal conclusions. These findings confirm that mastery of Qira'at is a crucial element for commentators and fuqaha (jurists) in producing comprehensive and contextual interpretations and formulations of Islamic law.